PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN KOMUNIKASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. AGUNG AUTOMALL CABANG SOEKARNO-HATTA PEKANBARU - Winda Febrya; Nuryant Nuryant; Rio J M Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
While the technique of data analysis in this study the authors use the method of SPSS (Statiscal Package Of Social Science). Based of the result of the analysis can be in the know that the style of leadership, discipline and communication work positively affects employee satisfaction at PT. Agung Auto mall Branches Soekarno-Hatta Pekanbaru. These there independent variables influence, either partially or simultan on the job satisfaction at PT. Agung Auto mall Branches Soekarno-Hatta Pekanbaru. Based on the result of this study the authors suggest that the company pay more attention to leadership style, as a leader should be able to give you more motivation to employees and provide an introduction to how importand result of an effort, put the interest of the group of personal things and create a work environment that discipline in order to avoid gaps social as well as provide examples and create good communication within the company in order to create employee satisfaction at PT. Agung Automall Branches Soekarno-Hatta Pekanbaru.Keywords: Styles Leadhersip, Discipline, and Communication.